Comparison study of energy management related certifications in Malaysia - Wahab Z.A.; Salleh A.A.M.; Kodio K.A.; Mohamed H. (American Institute of Physics Inc., 2024)
Applying energy management approach is an effective strategy to implement initiatives to reduce energy costs from energy saving measures. In implementing energy efficiency measures through energy management, standards are often being referred and used as the guides. Standards related to energy management can be classified into management standard and technical standard. Rating systems are often developed with specific requirements that will used to determine the level of rating to be achieved for specific project or building facilities. These requirements are grouped and managed in the form of points or scores for each requirement. For the recognitions or to gain credentials of the use of any standard, the next step for the organization is to obtain the third-party involvement through certification or rating based on chosen the standard or rating system. In Malaysia, there are locally and international energy management standards and green building rating systems that are referred and applied and this paper will explain and discuss further two energy management standards namely ISO50001:2018 Energy Management Systems - Requirements with Guidance for Use and ASEAN Energy Management Scheme (AEMAS) Energy Management Gold Standard (EMGS) and one rating system which is Green Building Index (GBI) in Malaysia. The adoption of energy management system standards and the use of rating system related too energy efficiency can play a significant role in promoting this shift toward more intensive and sustainable energy efficiency implementation in Malaysia through initiatives by the government and measures taken by users especially large energy users. 2023 AIP Publishing LLC.